Anthraquinones with antiplasmodial activity from the roots of rennellia elliptica korth. (Rubiaceae) - Osman, C.P.; Ismail, N.H.; Ahmad, R.; Ahmat, N.; Awang, K.; Jaafar, F.M. (MDPI AG, 2010)
Dichloromethane root extract of Rennellia elliptica Korth. showed strong inhibition of Plasmodium falciparum growth in vitro with an IC(50) value of 4.04 mu g/mL. A phytochemical study of the dichloromethane root extract has led to the isolation and characterization of a new anthraquinone, 1,2-dimethoxy-6-methyl-9,10-anthraquinone (1), and ten known anthraquinones: 1-hydroxy-2-methoxy-6-methyl-9,10-anthraquinone (2), nordamnacanthal (3), 2-formyl-3-hydroxy-9,10-anthraquinone (4), damnacanthal (5), lucidin-omega-methyl ether (6), 3-hydroxy-2-methyl-9,10-anthraquinone (7), rubiadin (8), 3-hydroxy-2-methoxy-6-methyl-9,10-anthraquinone (9), rubiadin-1-methyl ether (10) and 3-hydroxy-2-hydroxymethyl-9,10-anthraquinone (11). Structural elucidation of all compounds was accomplished by modern spectroscopic methods, notably 1D and 2D NMR, IR, UV and HREIMS. The new anthraquinone 1, 2-formyl-3-hydroxy-9,10-anthraquinone (4) and 3-hydroxy-2-methyl-9,10-anthraquinone (7) possess strong antiplasmodial activity, with IC(50) values of 1.10, 0.63 and 0.34 mu M, respectively.